Bioactive Compounds and Their Impact on Protein Modification in Human Cells - Prasad, Ankush; Rossi, Claudio; Manoharan, Renuka Ramalingam; Sedlářová, Michaela; Cangeloni, Lorenzo; Rathi, Deepak; Tamasi, Gabriella; Pospíšil, Pavel; Consumi, Marco (International journal of molecular sciences, 2022)
Reactive oxygen species (ROS) represent a group of molecules with a signaling role that are involved in regulating human cell proliferation and differentiation. Increased ROS concentrations are often associated with the local nonspecific oxidation of biological macromolecules, especially proteins and lipids. Free radicals, in general, may randomly damage protein molecules through the formation of protein-centered radicals as intermediates that, in turn, decay into several end oxidation products. Malondialdehyde (MDA), a marker of free-radical-mediated lipid oxidation and cell membrane damage, forms adducts with proteins in a nonspecific manner, leading to the loss of their function. In our study, we utilized U-937 cells as a model system to unveil the effect of four selected bioactive compounds (chlorogenic acid, oleuropein, tomatine, and tyrosol) to reduce oxidative stress associated with adduct formation in differentiating cells. The purity of the compounds under study was confirmed by an HPLC analysis. The cellular integrity and changes in the morphology of differentiated U-937 cells were confirmed with confocal microscopy, and no significant toxicity was found in the presence of bioactive compounds. From the Western blot analysis, a reduction in the MDA adduct formation was observed in cells treated with compounds that underlaid the beneficial effects of the compounds tested.
Keywords: malondialdehyde; bioactive compounds; Malondialdehyde; Free Radicals; malondialdehyd; nutraceuticals; reaktivní formy kyslíku; macrophage; antioxidants; Oxidative Stress; monocyte; protein modification; Oxidation-Reduction; Reactive Oxygen Species; reactive oxygen species; redox reactions; Humans; phorbol 12-myristate 13-acetate; volné radikály; oxidace-redukce; oxidační stres; lidé